Formulation of Metformin HCl Floating Tablet using HPC, HPMC K100M, and the Combinations - Lili Fitriani; Rudi Abdillah; Elfi Sahlan Ben (Jurnal Sains Farmasi & Klinis, 2017)
Floating tablet is one of the most suitable dosage forms that used for delivering long term drug release. The objective of this study was to evaluate Hydroxypropyl cellulose (HPC), Hydroxypropyl Methyl Cellulose (HPMC) K100M, and the combination as matrix in manufacturing floating tablets. Metformin HCl, an anti-diabetic, was used as a drug model. Metformin HCl floating tablet was manufactured by wet granulation method in three formulas using variation of matrix, which were 40% of HPC (F1), 40% of HPMC K100M (F2), combination of 20% HPC and 20% HPMC K100M (F3). Prior to tablet compaction, evaluation for granules were done which included moisture content, angle of repose using, bulk and tapped density, Hausner ratio, and compressibility. The evaluations of floating tablet were physical properties, floating ability, and in vitro drug release. The average of floating lag time for F1, F2, F3, were 7 minutes 13 seconds; 5 minutes 27 seconds; and 14 minutes 5 seconds, respectively. In addition, the floating time for F1 was 3 hours 16 minutes whereas F2, F3 were more than 48 hours. F2 showed the best floating ability to retain the drug release, which was 84.68% over 8 hours, while F1 and F3 were completely dissolved less than 6 hours.